Expandable Immunotherapeutic Nanoplatforms Engineered from Cytomembranes of Hybrid Cells Derived from Cancer and Dendritic Cells. Issue 18 (25th March 2019) - Liu, Wen‐Long; Zou, Mei‐Zhen; Liu, Tao; Zeng, Jin‐Yue; Li, Xue; Yu, Wu‐Yang; Li, Chu‐Xin; Ye, Jing‐Jie; Song, Wen; Feng, Jun; Zhang, Xian‐Zheng
Abstract: Using the cytomembranes (FMs) of hybrid cells acquired from the fusion of cancer and dendritic cells (DCs), this study offers a biologically derived platform for the combination of immunotherapy and traditional oncotherapy approaches. Due to the immunoactivation implicated in the cellular fusion, FMs can effectively express whole cancer antigens and immunological co‐stimulatory molecules for robust immunotherapy. FMs share the tumor's self‐targeting character with the parent cancer cells. In bilateral tumor‐bearing mouse models, the FM‐coated nanophotosensitizer causes durable immunoresponse to inhibit the rebound of primary tumors post‐nanophotosensitizer‐induced photodynamic therapy (PDT). The FM‐induced immunotherapy displays ultrahigh antitumor effects even comparable to that of PDT. On the other hand, PDT toward primary tumors enhances the immunotherapy‐caused regression of the irradiation‐free distant tumors. Consequently, both the primary and the distant tumors are almost completely eliminated. This tumor‐specific immunotherapy‐based nanoplatform is potentially expandable to multiple tumor types and readily equipped with diverse functions owing to the flexible nanoparticle options. Abstract : Using the cytomembranes of fused cells derived from tumor and dendritic cells, a tumor‐specific immunotherapeutic platform is engineered, which is capable of easy cooperation with other therapy means. The hybrid‐cytomembrane‐coated nanophotosensitizer demonstrates durable immunotherapy against primary tumors post‐photodynamic‐therapy (PDT) and PDT‐enhanced immunity toward irradiation‐free distant tumors.